FACTORS INFLUENCING ADOPTION OF ONE ACRE FUND PROJECT BY FARMERS IN KANDUYI SUB-COUNTY, KENYA - Khatete, Kizito Wamalwa; Matuli, Hadija Murenga; Bor, Erick Kiprono (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
This study assessed the level of adoption of One Acre fund (OAF) agricultural project and its influence on the livelihoods of beneficiaries in Kanduyi Sub-county, Bungoma County, Kenya. The study was appropriate because One Acre Fund management is set to implement it in the next 10 years with the aim of reaching 1 million farmers. The objective of the study was to establish factors that influence adoption of One Acre Fund project by farmers. The study premised on two theories; the innovation diffusion model and the sustainable livelihoods model. The theories complemented one another in explaining the study. Descriptive research design, survey and ‘before’ and ‘after’ designs were used in the study. The sample of the study was 116 heads of households who adopted OAF. Two OAF officials, two farmer field facilitators and two officials from ministry of Agriculture were key informants for the study. Purposive and snowball sampling techniques were used to get the desired sample. Questionnaire and interview schedule were used to obtain data from respondents. Descriptive statistics such as percentages and frequencies were used for data analysis. The study findings show that majority of OAF farmers were small scale women farmers with farm sizes of below 3 acres. Moreover, majority of the farmers had primary education and were below 39 years in age. OAF field officers and snow ball effect of friends played a crucial role in mobilizing farmers to join OAF, also good harvest, provision of inputs on credit, efficient training in field schools were key drivers in joining OAF. The study recommends that OAF introduces other crops like tomatoes and water melons among others, provide irrigation kits and introduce horticultural farming such as green house technology to further boost livelihoods of farmers.